Summer warming and increased winter snow cover affect Sphagnum fuscum growth, structure and production in a sub-arctic bog - Dorrepaal, Ellen; Aerts, Rien; Cornelissen, Johannes H. C.; Callaghan, Terry V.; Van Logtestijn, Richard S. P. (Global change biology, 2004)
Sphagnum mosses form a major component of northern peatlands, which are expected to experience substantially higher increases in temperature and winter precipitation than the global average. Sphagnum may play an important role in the responses of the global carbon cycle to climate change. We investigated the responses of summer length growth, carpet structure and production in Sphagnum fuscum to experimentally induced changes in climate in a sub‐arctic bog. Thereto, we used open‐top chambers (OTCs) to create six climate scenarios including changes in summer temperatures, and changes in winter snow cover and spring temperatures. In winter, the OTCs doubled the snow thickness, resulting in 0.5–2.8°C higher average air temperatures. Spring air temperatures in OTCs increased by 1.0°C. Summer warming had a maximum effect of 0.9°C, while vapor pressure deficit was not affected. The climate manipulations had strong effects on S. fuscum. Summer warming enhanced the length increment by 42–62%, whereas bulk density decreased. This resulted in a trend (P<0.10) of enhanced biomass production. Winter snow addition enhanced dry matter production by 33%, despite the fact that the length growth and bulk density did not change significantly. The addition of spring warming to snow addition alone did not significantly enhance this effect, but we may have missed part of the early spring growth. There were no interactions between the manipulations in summer and those in winter/spring, indicating that the effects were additive. Summer warming may in the long term negatively affect productivity through the adverse effects of changes in Sphagnum structure on moisture holding and transporting capacity. Moreover, the strong length growth enhancement may affect interactions with other mosses and vascular plants. Because winter snow addition enhanced the production of S. fuscum without affecting its structure, it may increase the carbon balance of northern peatlands.